Role of leaders’ positive mindset in mitigating the effects of crises on organizations: the case of Canadian organizations - Ouakouak, Mohammed Laid; Ouedraogo, Noufou; Hewapathirana, Gertrude I.; Zaitouni, Michel (My University, 2025)
Maintaining a positive mindset is important for leadership effectiveness and may even be more important in times of a crisis because such a mindset contributes to organizational survival and resilience. In this study, we examined whether leaders’ positive mindset helped to mitigate the harmful effects of the COVID-19 crisis on organizations and if so, how. To address this issue, we conducted an empirical study through LinkedIn with 165 participants working in various organizations in Canada. The results show that leaders’ positive mindset positively impacts leaders’ innovative behavior. However, leaders’ innovative behavior did not attenuate the negative effects of the COVID-19 crisis on organizations, except when we introduce the use of information and communication technology (ICT) and the provision of psychological support to employees as moderators. The implications of these findings for both theory and practice, as well as some future research directions are discussed.
Keywords: CVID-19 crisis; positive mindset; Canada; empirical study